(untitled) (Research, Society and Development, 2022)
Objectives:To identify the characteristics of individuals with Chronic Obstructive Pulmonary Disease (COPD) that exacerbate or not during a exercise training (ET) program, and check if any these groups are less likely to the benefits of ET. Methods:Individuals with COPD were evaluated for lung function, respiratory muscle strength, body composition, 6-minute walk test (6MWT), peripheral muscle strength, quality of life, functional status, dyspnea sensation in daily life (Medical Research Council [MRC] scale), anxiety and depression. All individuals performed a high-intensity exercise training (ET) program with aerobic exercises and strength training (three times/week, 12 weeks). For analysis, the individuals were separated into two groups (Group that Exacerbated [GE] and Group that did Not Exacerbate [GNE], and compared as to their characteristics. Results: 44 individuals completed the ET (26 in the GNE [FEV1 46±16%predicted] and 18 in the GE [FEV1 42±18 %predicted]). In pre-training, GE individuals were younger, more anxious and with worse forced vital capacity than GNE. After the ET, only the GE showed significant improvement in dyspnea (pre vs post-training: MRC 4 [3–4] vs 3 [2–4]; P=0.03) and only the GNE in the 6MWT (478 [424-519] vs 516 [467–558]; P<0.0001). Both groups showed improvement significant in the peripheral muscle strength. Finally, considering the comparison of the change post-pre ET, the GNE had a more marked improvement in quality of life and 6MWT. Conclusion: Individuals who exacerbate during an ET are less likely to benefit from ET, and training strategies tailored t are necessary.